2022
DOI: 10.3390/cells11132011
|View full text |Cite
|
Sign up to set email alerts
|

T-Lymphocyte Interactions with the Neurovascular Unit: Implications in Intracerebral Hemorrhage

Abstract: In the pathophysiology of hemorrhagic stroke, the perturbation of the neurovascular unit (NVU), a functional group of the microvascular and brain intrinsic cellular components, is implicated in the progression of secondary injury and partially informs the ultimate patient outcome. Given the broad NVU functions in maintaining healthy brain homeostasis through its maintenance of nutrients and energy substrates, partitioning central and peripheral immune components, and expulsion of protein and metabolic waste, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The acute and chronic phases of IS and the long-term effects of stroke are greatly affected by the immune system ( 10 ). The immune response after IS involves innate and adaptive immunity in the central and peripheral nervous systems ( 11 ). Targeting regulatory immunity is a promising approach for reducing stroke-related dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The acute and chronic phases of IS and the long-term effects of stroke are greatly affected by the immune system ( 10 ). The immune response after IS involves innate and adaptive immunity in the central and peripheral nervous systems ( 11 ). Targeting regulatory immunity is a promising approach for reducing stroke-related dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there have been a few reported cases of brucellosis complicated by HS. Previous studies indicate the involvement of infiltrating T lymphocytes in the pathophysiological process of cerebral hemorrhage ( 12 ). However, the precise mechanism by which brucellosis contributes to the occurrence and progression of stroke requires further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have found that T cells can patrol the cerebrospinal fluid in the healthy CNS to conduct immune surveillance ( 107 ). And after ICH, activated T cells can cross the BBB and contribute to brain injury through a number of mechanisms such as microvascular dysfunction, neuronal apoptosis, inflammatory molecules production, neutrophil recruitment, and interaction with microglia ( 108 ). The major subtypes of T cells include CD4+ Th cells (including Th1, Th2, and Th17 cells), CD8+ cytotoxic T cells, memory T cells, and T-regulatory (Treg) cells.…”
Section: Mechanism Of Microrna In Modulating Neuroinflammation After Ichmentioning
confidence: 99%
“…They have different molecular expression profiles and cellular functions, with some mainly exerting injurious effects and others being reparative after ICH. Among them, CD4+ T cells are the predominant populations in the post-ICH brain milieu ( 108 ). Studies suggest that many miRNAs can serve as positive or negative regulators of T cell development and function, exemplified by the fact that models with certain miRNA deficiency can have CD4+ and CD8+ T cell dysfunction ( 109 ).…”
Section: Mechanism Of Microrna In Modulating Neuroinflammation After Ichmentioning
confidence: 99%